Mobile Mathematics Development: Sample Space and Probability for Critical Thinking and Problem Solving - Umam, Khoerul; Kusumawati, Erna; Setiadi, Hari; Bin Awang, Isha (JURNAL PENDIDIKAN MATEMATIKA, 2025)
Students' critical thinking and mathematical problem-solving skills are important elements in learning mathematics; however, facts in the field still provide notes on the average learning outcomes in the material of sample spaces, and simple event probabilities are still low. This study aims to develop a mobile-based mathematics learning application to improve students' critical thinking and mathematical problem-solving skills. This study uses the ADDIE development design (analysis, design, development, implementation, evaluation) and quasi-experimental methods with a pre-test-post-test design in the experimental and control groups. The study subjects were 11th-grade public and private high school students, with a total of 145 students participating. The instruments include critical thinking and mathematical problem-solving tests based on established indicators. Quantitative analysis uses a paired t-test. The results showed a significant increase in the average score of students in the experimental group with critical thinking skills (experiment 88.77, control 72.65) and mathematical problem solving (experiment 86.55, control 76.54) after using the application. The development of mobile learning applications on the material of sample spaces and simple events can effectively improve the critical thinking and mathematical problem-solving skills of high school students. Keywords: Critical Thinking Skills, Problem Solving Skills, Mobile, Mathematics Learning